Sastra Arab Modern dan Pengaruh Pers: Tinjauan Historis dari Era Nahdah hingga Digital - Anir Syam Azisyah; Haniah Haniah; Muhsin Muhsin (Jurnal Al-Hibru, 2026)
The development of modern Arabic literature is closely linked to the evolution of press and media in the Arab world. Since the Nahdah period, newspapers, magazines, and later electronic and digital media have played a significant role in shaping literary production, dissemination, and reception. This study aims to analyze the development of Arab press and media, examine their role in disseminating modern Arabic literature, and explore their contribution to the transformation of literary genres, language styles, and reading communities. This research employs a qualitative library research method using a historical-descriptive approach and content analysis. Data were collected from books, scholarly journals, and other relevant academic sources concerning Arabic press, media, and modern Arabic literature. The findings reveal that media have functioned not only as channels of literary dissemination but also as agents of literary transformation, influencing genres, language practices, intellectual networks, and the relationship between authors and readers across different historical periods.